2020
DOI: 10.1002/eqe.3351
|View full text |Cite
|
Sign up to set email alerts
|

Interstory drift ratio associated with performance objectives for shallow‐buried multistory and span subway stations in inhomogeneous soil profiles

Abstract: The interstory drift ratios (IDRs) associated with the performance objectives for the underground structure are not well defined. In this paper, four levels of performance objectives are defined for shallow-buried subway station structure: operational, immediate occupancy, life safety, and collapse prevention. In order to develop IDRs corresponding to these performance objectives, 18 subway station structures were selected for this study. Pushover analyses were conducted using three-dimensional finite-element … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The specified seismic drift ratio limits for rectangular stations are prescribed as 0.1%, 0.37%, 0.77%, and 1.10% for operational, immediate occupancy, life safety, and collapse prevention performance levels without considering vertical ground motion. 68 Based on the quasi-static test results obtained from this study, it is evident that when the drift ratio exceeds 1.10%, the damping ratio significantly increases while stiffness decreases notably. When the axial compression ratio of a column is 0.40, the applied load of the column specimen enters the descending phase, consistent with the suggested drift ratio limit of 1.10% for collapse prevention performance level.…”
Section: Quantification Of the Hysteretic Behaviormentioning
confidence: 73%
“…The specified seismic drift ratio limits for rectangular stations are prescribed as 0.1%, 0.37%, 0.77%, and 1.10% for operational, immediate occupancy, life safety, and collapse prevention performance levels without considering vertical ground motion. 68 Based on the quasi-static test results obtained from this study, it is evident that when the drift ratio exceeds 1.10%, the damping ratio significantly increases while stiffness decreases notably. When the axial compression ratio of a column is 0.40, the applied load of the column specimen enters the descending phase, consistent with the suggested drift ratio limit of 1.10% for collapse prevention performance level.…”
Section: Quantification Of the Hysteretic Behaviormentioning
confidence: 73%
“…Four damage states were defined, using the interstory drift ratio θ as EDP. The thresholds of damage states were defined following Du et al [92], who performed a series of pushover analyses on 18 actual subway stations found in several cities in China. Stations of various shapes (i.e., two story, two spans; two story, three spans; three-story, three spans) were examined, with local site conditions accounted for in the pushover analyses.…”
Section: Mountain Tunnels and Tunnels In Rockmentioning
confidence: 99%
“…The maximum interstory drift ratio θ was used as EDP. Five damage states were defined, namely normal operational (NO), immediate operational (IO), reparable operational (RO), irreparable (IR) and complete collapse (CC), with the relevant thresholds being defined as per Du et al [92] and Zhang et al [93]. Based on the analyses results, analytical fragility curves were proposed using Sustained Maximum Acceleration (SMA) as IM for the assessment of the subway station in soil classes I and II, and the Velocity Spectrum Intensity (VSI) as IM for the assessment of the subway station in soil classes III and IV.…”
Section: Mountain Tunnels and Tunnels In Rockmentioning
confidence: 99%
See 2 more Smart Citations